2018
DOI: 10.1007/s00299-018-2317-2
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan oligosaccharides affect xanthone and VOC biosynthesis in Hypericum perforatum root cultures and enhance the antifungal activity of root extracts

Abstract: Water-soluble chitosan oligosaccharides (COS) affect xanthone and volatile organic compound content, as well as antifungal activity against human pathogenic fungi of extracts obtained from Hypericum perforatum root cultures. Several studies have demonstrated the elicitor power of chitosan on xanthone biosynthesis in root cultures of H. perforatum. One of the major limitations to the use of chitosan, both for basic and applied research, is the need to use acidified water for solubilization. To overcome this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
0
13
1
Order By: Relevance
“…The highest g X was 8.44 for H. tomentosum , transformed with A. rhizogenes A4 . This value is higher than previously reported data for auxin‐induced cultures . Impressively, g X reported in the current study was four to eight times higher than the previously reported values for shake flask cultivations of SJW root cultures (Table ) and the aforementioned hairy root cultures.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…The highest g X was 8.44 for H. tomentosum , transformed with A. rhizogenes A4 . This value is higher than previously reported data for auxin‐induced cultures . Impressively, g X reported in the current study was four to eight times higher than the previously reported values for shake flask cultivations of SJW root cultures (Table ) and the aforementioned hairy root cultures.…”
Section: Resultscontrasting
confidence: 78%
“…Thus, fixing these two factors might end in reproducible growth factor g X through years. Within the same scenario, comparing the growth factors of root cultures developed at the Italian laboratory (Table ) demonstrated that all cultures possessed similar values even after 8 years of repeated re‐establishment of these cultures, which might be explained by the imitated use of the same source of the explants. Correspondingly, the difference in g X values of the cultures developed in the Korean laboratory was minor when starting with the same inoculum size (Table ).…”
Section: Resultsmentioning
confidence: 93%
“…Exogenous chitosan reportedly interacts with chitin synthase, and chitin deacetylase in plants, to produce chitosan oligomers that are responsible for signal perception in cells, leading to the activation of various genes, including genes of the ROS pathway [50,70,71]. Elicitor molecules have been used to stimulate a broad range of responses including defense mechanism [72] in field conditions as well as in vitro cultures for elicitation of secondary metabolites [73,74,75,76]. However, it was reported earlier that acetic acid alone itself may exert some effect [77].…”
Section: Discussionmentioning
confidence: 99%
“…The attachment of prenyl moieties increases the lipophilicity of the resulting products, leading to enhanced interaction with biological membranes and hence increased biological activities (Alhassan et al ., ; Chen et al ., ). Prenylated constituents function as chemical defenses against microorganisms (Franklin et al ., ; Tusevski et al ., ; Badiali et al ., ). Xanthones act as both preformed phytoanticipins and induced phytoalexins (Xiao et al ., ; Tocci et al ., ).…”
Section: Introductionmentioning
confidence: 97%